Change in Student Mindset Toward Entrepreneur an Action Research - Rahayu, Amy Y.S. (UI Scholars Hub, 2014)
In general, students want to complete their study faster, graduate and get a job, but in fact the unemployment rate is open of the graduates have increased. Students who have been prepared and furnished with specific skills and expertise increasingly help the student’s preparedness to face undesirable conditions and only become job-seeker, and not as job-provider. Under this circumstance, the study of change in the student mindset toward entrepreneurship is necessary considered to find the right approach in changing people mindset toward the generation of creativity and innovation of the valuable works. This further expectation can help developing students a sense of confidence and their preparedness to navigate the real world after graduation. This research used an action research approach in the form of guidance based on a model of creative economic development and the process model of creativity-innovation-entrepreneurial, through six steps of guidance. The result showed that first, the process of transformation comprising guidance toward change in the mindset of participants run quite well; however, there are still many shortcomings, especially in terms of participants’ commitment and ability to develop the creative product. Second, the creation of space for the development of creative ideas, through motivation and awareness of participants, though not yet perfect and there are still barriers, such as the timing and lecture schedule.